EVALUATION OF SOLID WASTE MANAGEMENT AT UNIVERSITY X JAKARTA - Azteria, Veza; Salsanabilla, Wafiqa; Utami, Desyawati (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Most of the waste produced in the university environment comes from the canteen. The accumulation of waste in the university environment is due to the lack of proper waste management. The sorting, collection, transportation, and recycling process has not been carried out, and even education and awareness of all university components have not been maximized. This research aims to evaluate waste management in the university environment using qualitative methods with a descriptive design. Respondents consisted of 5 informants, namely key informants (management section), primary informants (head in charge of university cleanliness, janitor, waste collection officer), and supporting informants (campus security officers). Data was collected using in-depth interviews, field observations, and document reviews, which were then validated using source and method triangulation methods. The research results stated that there were no operational standards in waste management in the university environment, unscheduled transportation schedules, and no community awareness of the need to sort waste properly. There needs to be active participation of the entire academic community and transparent policies in managing campus waste.